The innovative lean machine : synchronizing people, branding, and strategy to win in the marketplace - Sgroi, Anthony (CRC Press, 2015)
"Businesses require three optimized core components to run effectively: strategy, people, and branding. This book uses Lean principles along with graphics, charts, and tables to explain these three important components for every business. The book presents a series of visual frameworks that allow readers to readily apply the format with little or no difficulty. With the aid of many examples, illustrations, tables and graphics, the book details methods for transforming any business into a more effective business. The concepts in this book come from the visual method of delivery using Lean principles"--